Benin : Fourth Review Under the Poverty Reduction and Growth Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper assesses Benin's Fourth Review Under The Poverty Reduction and Growth Facility (PRGF). Macroeconomic performance remained broadly in line with the objectives of the PRGF-supported program in 2002. All performance criteria for end-September 2002 were met, and the four structural benchmarks were observed by end-December 2002. However, spending on health and education remained below quantitative benchmarks, and the civil service reform continued to stall. The authorities finalized the poverty reduction strategy for 2003-05, which aims at achieving strong economic growth and reducing poverty, while maintaining financial stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet